US Library Institutions as Centers for Women’s and Gender Studies and Gender Education - Cherniavska Lina (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2020)

(untitled)
This article discusses US universities and national libraries more than 30 years' experience in work as centers for the initiation and education of citizens, as well as leading research centers for women and gender studies in American society. Attention is focused on the relevance of informing the population as a whole about the principles of gender equality, quality information and research on this issue. The main attention is paid to the experience of library institutions systematic work in search for new forms of cooperation between students and teachers, scientists involved in research in the field of female and gender studies. It is noted that thanks to the active cooperation between library workers and library resources users in the field of women and women and gender studies, libraries have become effective participants in the education system and scientific work in general. The principles of building library information databases for the study of women and the gender issue, as well as the effective navigation systems created by librarians in extensive library collections, are examined. This task is very urgent, because often the information researchers require is scattered across all library collections. Great progress has been noted in the field of library and information support for education and science, in particular, the creation of web portals and library sites, the formation of a full-fledged industry information resource, electronic catalogs, full-text databases, electronic gender libraries, as well as cooperation between different libraries. Considering the role of American libraries in organizing women's and gender studies, we can conclude that they not only play the role of leading information and document centers, training centers, but they themselves become significant research institutions. Collections of some libraries are parts of national and world heritage.